Guardian of Ancient Egypt : studies in honor of Zahi Hawass - Hawass, Zahi A.,; Kamrin, Janice, 1966-; Bárta, Miroslav,; Ikram, Salima,; Lehner, Mark,; Megahed, Mohamed, (Charles University, Faculty of Arts, 2020)
To the Studies in Honor of Zahi Hawass contributed more than 100 authors. These 3 vols. edited 5 Egyptologists, preface wrote Khaled el-Enany, Minister of Tourism and Antiquities in Egypt. Dr. Zahi Hawass is the most famous Egyptologist in the world. He is much more than his public persona, as the many wonderful tributes in this volume attest. He is an experienced archaeologist, a serious and significant scholar.00Zahi was a Senior and soon Chielf Inspector at Giza. He was a graduate student at the University of Pennsylvania. Zahi today embodies a living history of modern Egyptology, especially in the field of pyramid studies. Studies include Zahiþs biography and bibliography.